2019
DOI: 10.1002/adsc.201900641
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Conditions for the Regiodivergent Direct Arylations at C2‐ or C5‐Positions of Oxazoles using Phosphine‐Free Palladium Catalysts

Abstract: Two sets of reaction conditions for the regiodivergent C2-or C5-direct arylations of oxazole are reported. In both cases, phosphine-free catalysts and inexpensive bases were employed allowing the access to the arylated oxazoles in moderate to high yields. Using Pd(OAc)2/KOAc as catalyst and base, regioselective C5arylations were observed; whereas, using Pd(acac)2/Cs2CO3 system, the arylation occurred at the C2-position of oxazole. The higher reactivity of C5-H bond of oxazole as compared to the C2-H bond in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Indeed, in 2019 we reported that the regioselectivity of the direct arylation of oxazole can be controlled using the appropriate base [7] . From phosphine‐free Pd(OAc) 2 catalyst associated to KOAc, regioselective C5‐arylations, which likely proceed via a CMD mechanism, were observed (Scheme 1, a).…”
Section: Nature Of the Base Or Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in 2019 we reported that the regioselectivity of the direct arylation of oxazole can be controlled using the appropriate base [7] . From phosphine‐free Pd(OAc) 2 catalyst associated to KOAc, regioselective C5‐arylations, which likely proceed via a CMD mechanism, were observed (Scheme 1, a).…”
Section: Nature Of the Base Or Solventmentioning
confidence: 99%
“…We also studied the reactivity of 2‐aryloxazoles using Pd and Ru catalysts [40] . From 2‐aryloxazoles and a set of electron‐rich or ‐poor aryl bromides, in the presence of Pd(OAc) 2 catalyst, the 2,5‐diaryloxazoles were obtained with complete regioselectivity and high yields (Scheme 22, a).…”
Section: Nature Of the Metal Of Catalystsmentioning
confidence: 99%
“…For highly substituted oxazoles some de novo syntheses have been described that allow for their assembly, [17] but are difficult to apply for late‐stage diversification. Moreover, (catalytic) C–H activation of the oxazole ring has been reported, [18–20] such as C5‐functionalization by imidation, [21] alkylation, [22] acylation, [23] alkenylation, [24] or arylation [25] . Several protocols for regioselective C−H activation have been developed, [19,20,26,27] but typically were applied to structurally simple oxazoles stabilized by a C2‐(hetero)aryl group.…”
Section: Figurementioning
confidence: 99%
“…Moreover, (catalytic) C–H activation of the oxazole ring has been reported, [18–20] such as C5‐functionalization by imidation, [21] alkylation, [22] acylation, [23] alkenylation, [24] or arylation [25] . Several protocols for regioselective C−H activation have been developed, [19,20,26,27] but typically were applied to structurally simple oxazoles stabilized by a C2‐(hetero)aryl group. Alternatively, transition metal‐mediated cross‐couplings of 5‐bromooxazoles [27–29] and oxazolyl‐5‐ethers [30] have been realized, but often suffer from limited substrate scope as well as modest stability of the oxazole ring such activated.…”
Section: Figurementioning
confidence: 99%
“…Among these, aryl halides are a cost-effective option that is commercially available in a wide range from different suppliers. The described methodologies for the C 2arylation of 5-aryl-oxazole and benzoxazole using aryl halides report an activation by palladium catalysts (such as Pd(OAc) 2 , 38 Pd(acac) 2 , 50 PdCl 2 (dppf), Hermann-Beller palladacycle, 51 Pd(phen) 2 (PF 6 ) 2 , 52 and Pd(PPh 3 ) 4 53,54 ), nickel catalysts (such as NiBr 2 , 55 Ni(OAc) 2 56 and Ni(COD) 2 57 ), or by equimolar amounts of copper(I) salts (mainly CuI). 58,59 In these methods, the use of both carbonate or alkoxide bases is reported, which suggests that the reaction might go through S E Ar-or CMD-type mechanisms depending on the conditions.…”
Section: Figure 1 Example Of Oxazole-containing Natural Products and Synthetic Molecules With Biological Activitiesmentioning
confidence: 99%